A new design of electronic control unit involving microcontroller to determine important parameters for target species in forest - Özcan, Gonca Ece; Çіçek, Osman; Enez, Korhan; Yildiz, Mustafa (Springer Science and Business Media LLC, 2018)
Forests, a valuable source provided by nature to living beings, are indispensable for many living organisms; hence, it is important to ensure the sustainability of forests. Determining the factors that exposure threats to the forests, executing protective methods against them and putting these methods into practise are important for the ecological cycle. Bark beetles, which have destructive effects on the ecosystem, are one of the factors that expose a threat to forests. Therefore, monitoring of these species and determination of effective control strategies are increasingly gaining importance in forestry. Conventional pheromone traps, which are being currently used, provide limited information on flight times of target species. Therefore, the technological development of the capture systems of these traps will determine future control trends. Hence, pheromone traps with electronic control unit were prepared in earlier (ѵ1) and new designed (ѵ2) versions. In ѵ2, 97.5% of target species were counted, and instant temperature, humidity and time parameters at the time of capture were recorded at a practiced field work for the system. In addition to the instant parameters recorded in ѵ2, an anemometer used for measuring wind speed, which is considered to have influence on the behaviour of target species, was incorporated into the system. In the trials, the counting success rates under daylight and darkness conditions for Ips sexdentatus adults were 98.1 and 97%, whereas the counting success rates for Pityocteines curvidens adults, which are smaller in size, were 96 and 99%, respectively. In conclusion, data obtained by recording the amount of target species along with the capture moment and parameters related to this will be very useful and provide determinative in the management of target species.
Keywords: Coleoptera; Temperature; Animals; Forestry; Forests; Ecosystem; Environmental Monitoring; 13. Climate action; 15. Life on land